Klum@Gtap: Introducing Biophysical Aspects of Land-Use Decisions Into a General Equilibrium Model A Coupling Experiment - Kerstin Ronneberger; Maria Berrittella; Francesco Bosello; Richard S.J. Tol (Fondazione Eni Enrico Mattei (FEEM), 2006)
In this paper the global agricultural land use model KLUM is coupled to an extended version of the computable general equilibrium model (CGE) GTAP in order to consistently assess the integrated impacts of climate change on global cropland allocation and its implication for economic development. The methodology is innovative as it introduces dynamic economic land-use decisions based also on the biophysical aspects of land into a state-of-the-art CGE; it further allows the projection of resulting changes in cropland patterns on a spatially more explicit level. A convergence test and illustrative future simulations underpin the robustness and potentials of the coupled system. Reference simulations with the uncoupled models emphasize the impact and relevance of the coupling; the results of coupled and uncoupled simulations can differ by several hundred percent.
Keywords: C68; Q15; 330; Land-Use Change; Computable General Equilibrium Modeling; Integrated Assessment; Climate Change; Landwirtschaftliche Bodennutzung; Allgemeines Gleichgewicht; Klimaveränderung; Welt